EFEK PSIKOSOSIAL PADA PERAWAT PEREMPUAN YANG MENJALANI PERAN GANDA - Faulis Apriani; Lina Dewi Anggraeni (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Nurses women who have got married and work is a woman with a dual role. The existence of a dual role demanded a woman come with responsibilities as housewive and employee. The breakup of liability often makes into focus. In his work as a professional nurse is required to perform tasks and obligations so it can't be denied that will have an impact on the individual's psychosocial and led to a decline in the quality of work. In working as a nurse professional prosecuted duties and their obligations and cannot be denied that will have an impact on psychosocial these individuals. The research aims to understand psychosocial effect in women who underwent: the dual role as a nurse work 3 shift and housewives. The methodology used was a qualitative methodology by approach phenomenology descriptive. Eight nurses interviewed in April - July after chosen by 2018 technique purposive sampling. Data in a Collaizi analysis. Research identifies 4 themes that: 1 ) the changes for, 2 ) strategy change, 3 ) supporting factors performing a role double and 4 ) the barrier the dual role. The result of this research expect nurse increase his personal responsibility as a nurse who works 3 shift and responsibilities as a housewife, in addition substitution the role of is necessary to resolve the conflict that occurs, not only that family encouragement and workplace could also help relieve conflict the role.